EKSPRESI RELIGI ISLAM DALAM NOVEL HAJI BACKPACKER KARYA AGUK IRAWAN MN - Annajmi Sakinah; Abdul Razak; Hadi Rumadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study discusses the Islamic Religious Expression in the Novel Haji Backpacker Aguk work Irawan MN . This study also discusses the description of Islamic religious expression found in the novel Haji Backpacker Aguk work Irawan MN. This study used a qualitative approach and descriptive method that aims to describe how Islamic religious expression contained in the novel Holy Woman Shahraz Qaisra work . Results of this study is to interpret the description of Islamic religious expression found in the novel Haji Backpacker Aguk work Irawan MN . The results also as a form of documentation of Islamic religious expression that exist in the novel Haji Backpacker Aguk work Irawan MN.Keywords: Islamic Religious Expression, Novel Haji Backpacker, Aguk Irawan MN